Alarming decline of bovids in Kasanka National Park, Zambia: A case study of the puku antelope (Kobus vardonii). (5th January 2021) - Rduch, Vera; Jentke, Thalia
Abstract: Knowledge about antelope populations and their status is a key for conservation. In November 2019, we used distance sampling to perform a re‐survey of the bovid species in Kasanka National Park, Zambia, with a focus on the puku ( Kobus vardonii ). Data collection and subsequent analyses were of the same design as in a previous survey in 2009–2010. This allowed for the direct comparison between survey periods, especially for the data collected in November 2010 and 2019. The estimated puku population size decreased from 5, 038 (range 3, 268–7, 238) animals in 2009–2010 to 819 (range 250–2, 708) animals in 2019, representing an 84% decline. Smaller group sizes were observed. Changes in population structure (decline in male abundance, fewer male groups) and spatial distribution (decline in population density, especially along the park boundaries) of puku showed signs of increased poaching activities in Kasanka National Park. Also, puku became more vigilant and demonstrated significantly longer flight distances in 2019 in comparison with 2010. A strong decline in puku in combination with clear signs of poaching, as well as the reduced species richness and sightings of other bovids, should become an agenda for long‐term conservation of Kasanka National Park. Résumé: La connaissance des populations d'antilopes et de leur statut est essentielle en matière de conservation. En novembre 2019, nous avons utilisé une méthode d'échantillonnage des distances pour effectuer une nouvelle enquête sur les espèces de bovidés présentes dans le parc national de Kasanka, en Zambie, en mettant l'accent sur le puku ( Kobus vardonii ). La collecte des données et les analyses subséquentes étaient de même nature que dans une étude précédente effectuée en 2009‐2010. Cela a permis une comparaison directe entre les périodes d'étude, en particulier concernant les données collectées en novembre 2010 et 2019. La taille estimée de la population de puku est passée de 5 038 (fourchette 3268‐7238) animaux en 2009‐2010 à 819 (fourchette 250‐2708) animaux en 2019, soit une baisse de 84%. Des groupes plus petits ont été observés. Les changements dans la structure de la population (déclin de l'abondance des mâles, moins de groupes de mâles) et dans la répartition spatiale (déclin de la densité de la population, en particulier le long des limites du parc) du puku ont démontré des signes d'augmentation des activités de braconnage dans le parc national de Kasanka. Par ailleurs, le puku est devenu plus vigilant et a montré des distances de fuite beaucoup plus importantes en 2019 qu'en 2010. Un fort déclin du puku associé à des signes évidents de braconnage ainsi qu'une diminution de la richesse en espèces et de la présence d'autres bovidés observés devraient donner lieu à un programme de conservation à long terme du parc national de Kasanka.